Religion in Period of Adolescence and Youth - Rajabov, Elvin (Scholarya Demo Journal of Ruby, 2019)
Period of adolescence and youth differs greatly from other periods of human life according to their characteristics. There are also differences in the religious thoughts and behaviors of adolescents and young people. In this article, religious thoughts and behaviors are stated in adolescents and young people. this article also explores the religious thoughts and behaviors of adolescents and young people in Islamic aspect. In the first part of this article, psychological situations specific to adolescence and youth are analyzed. As a result, it was stated that adolescents and young people are very sensitive and have emotional approach to the events they witness. Due to the development of the mind during this period, adolescents frequently think about EÖ:issues, analyze them and quit imitation. The second part of the article deals with religious thoughts and behaviors of adolescents and young people. As a result, it was reported that young people thought deeply about religious issues, analyzed them, and completely distanced themselves from period of childhood imitation. it is emphasized that the unlike childhood period, adolescents do not have an anthropomorphic thought of God, they think of God as unparalleled in all things and has no partner. Another feature of this period is scepticism and reanalysis of the thoughts accepted imitatively in childhood. Repentance, regret and return to religion are also emphasized as characteristic features. In the third part of the article, religious thoughts and behaviors of adolescents and youth are analyzed from an Islamic perspective. Religious thoughts in the youth period are shown with examples from the Qur’an and hadiths which are the main sources of Islam.